A Brief Analysis of How to Effectively Implement Performance Appraisal in Landscaping Institutions - Dong, Zhang (Journal of Theory and Practice of Social Science, 2023)
Landscaping institutions have a very important meaning to our country's green development. Nowadays, with the continuous improvement of social development level, the internal management of landscaping institutions should also be adjusted and changed accordingly, especially the performance appraisal of personnel. However, there are many deficiencies in the personnel performance appraisal, for which effective measures should be taken to improve the construction of the performance appraisal system and fully mobilize the enthusiasm of the staff of ft landscaping institutions.